Spectrum of Hepatits B Infection Among Patients Attending Liver Unit in Nepalgunj Medical College – Kohalpur - Khadka, Dipendra; KC, Sudhamshu; Karki, Niyanta; Khadka, Sandip; Regmi, Kiran (Journal of Nepalgunj Medical College, 2018)
Introduction: Hepatitis B infection is a global problem. Hepatitis B virus (HBV) infection related liver disease is also not an uncommon problem in our country too. Reports regarding pattern of chronic HBV infection are also lacking. The aim of the present study was to determine the spectrum of chronic HBV infection among patients attending the liver clinic in a tertiary care center. Method: A hospital based descriptive cross-sectional study was carried out in Liver unit of Nepalgunj Medical College, Kohalpur, from April 2018 to November 2018. All patients with HBsAg positive were further tested for HBeAg, HBeAb, HBV DNA quantitative and liver function test. Ultrasound examination was advised for any evidence of chronic liver disease. Staging was done according to viral serology, liver biochemistry and ultrasonography of liver Results: Total patients enrolled were 119. Majority of patents were in between 30-60 years (51.3%) with male predominance 59.7%. Most of patients were in the stage of HBeAg negative chronic infection 66.4% with normal transaminase and HBV DNA <2000 IU/ML. Majority of patients having unknown source of infection 90.8%. Incidental detection (67.2%) was common mode of detection. Conclusions: Majority of patients were in HBeAg negative chronic hepatitis B infection phase with normal transaminase and low HBV DNA not requiring treatment.